2017
DOI: 10.1080/02699931.2017.1304359
|View full text |Cite
|
Sign up to set email alerts
|

Biases in attention and interpretation in adolescents with varying levels of anxiety and depression

Abstract: This is the first study to investigate multiple cognitive biases in adolescence simultaneously, to examine whether anxiety and depression are associated with biases in attention and interpretation, and whether these biases are able to predict unique variance in self-reported levels of anxiety and depression. A total of 681 adolescents performed a Dot Probe Task (DPT), an Emotional Visual Search Task (EVST), and an Interpretation Recognition Task. Attention and interpretation biases were significantly correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…Using the same stimuli makes it possible to test this pathway and to manipulate individual biases and observe their effect on subsequent biases in the pathway. However, using different stimuli and methods may offer greater confidence in the generalizability of the data across different biases and reduces the inflating effect of common method variance (e.g., Klein et al ., ). In addition, the tasks used in this study are easy to administer in a wide range of settings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Using the same stimuli makes it possible to test this pathway and to manipulate individual biases and observe their effect on subsequent biases in the pathway. However, using different stimuli and methods may offer greater confidence in the generalizability of the data across different biases and reduces the inflating effect of common method variance (e.g., Klein et al ., ). In addition, the tasks used in this study are easy to administer in a wide range of settings.…”
Section: Discussionmentioning
confidence: 97%
“…() highlight that relatively little research has been conducted with adolescents, particularly with adolescents who have elevated symptoms of depression or have a diagnosis of depression. Recently Klein, de Voogd, Wiers, and Salemink () assessed attention and interpretation bias in adolescents recruited from the community. Biases in attention and interpretation explained small but significant variance in severity of depression and anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Long-standing integrative models of psychopathology emphasise that maladaptive cognitive and/or learning factors likely co-exist in anxious individuals and, importantly, interrelate to influence symptoms (Hirsch, Clark, & Mathews, 2006;Everaert, Koster, & Derakshan, 2012;Waters & Craske, 2016). The "combined cognitive bias" hypothesis suggests that these "cognitive processes are likely to work together in various ways serving to maintain specific emotional disorders" (Hirsch, et al, 2006), leading to some studies considering how attention, memory and/or interpretation biases explain common (but also distinct variance) on youth anxiety (Watts & Weems 2006;Klein et al, 2014;Klein, de Voogd, Wiers, & Salemink, 2017). However, a more important tenet of this hypothesis and a recent integrative youth anxiety model (Waters &Craske, 2016) is that certain cognitive factors inter-relate with other (Hirsch et al, 2006) and/or with learning factors (Waters & Craske, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental studies have reported information processing biases in depression, including increased engagement with negative information and excessively negative interpretations of emotional events (45,46). Our analyses suggest that intersubject synchronization is related to the emotional content of the stimulus.…”
Section: Emotional Movie Content Weakens the Relationship Between Iscmentioning
confidence: 54%